Efficacy and safety of PulseRider for treatment of wide-necked intracranial aneurysm—A systematic review and meta-analysis. Issue 1 (February 2021) - Pranata, Raymond; Yonas, Emir; Vania, Rachel; Sidipratomo, Prijo; July, Julius
Objective: PulseRider is a novel self-expanding nickel-titanium (nitinol) stent for treatment of wide-necked aneurysms, which is commonly located at the arterial branches in the brain. This systematic review and meta-analysis aims to assess the efficacy and safety of PulseRider for treatment of wide-necked intracranial aneurysm. Method: We performed a systematic literature search on articles that evaluate the efficacy and safety of PulseRider-assisted coiling of the wide-necked aneurysm from several electronic databases. The primary endpoint was adequate occlusion, defined as Raymond-Roy Class I + Raymond-Roy Class II upon immediate angiography and at six-month follow-up. Results: There were a total of 157 subjects from six studies. The rate of adequate occlusion on immediate angiography was 90% (95% CI, 85%–94%) and 91% (95% CI, 85%–96%) at six-month follow-up. Of these, Raymond-Roy Class I can be observed in 48% (95% CI, 41%–56%) of aneurysms immediately after coiling, and 64% (95% CI, 55%–72%) of aneurysms on six-month follow-up. Raymond-Roy Class II was found in 30% (95% CI, 23%–37%) of aneurysms immediately after coiling, and 25% (17–33) after six-month follow-up. Complications occur in 5% (95% CI, 1%–8%) of the patients. There were three intraoperative aneurysm rupture, three thrombus formation, three procedure-related posterior cerebral artery strokes, one vessel dissection, and one delayed device thrombosis. There was no procedure/device-related death. Conclusions: PulseRider-assisted coiling for treatment of patients with wide-necked aneurysm reached 90% adequate occlusion rate that rises up to 91% at sixth month with 5% complication rate.